Orthogonal Stimulus Response Method Optimization of Essential Oil Combinations from Magnolia alba, Cryptocarya massoia, and Melaleuca alternifolia for Antioxidant and Anti-Cutibacterium acnes Activities - Ayudianti, Prida; Rahmayanti, Mayu; Maulina, Novia; Muslikh, Faisal Akhmal; Aluzia, Aufary Naurah; Azzahra, Fatimah; Ma’arif, Burhan (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to optimize a combination of white champaca oil (Magnolia alba), massoia bark oil (Cryptocarya massoia), and tea tree oil (Melaleuca alternifolia) as antibacterial and antioxidant agents using the Orthogonal Stimulus Response Method (OSRM) with a Taguchi L4 (2³) design. Antibacterial activity was evaluated using the well diffusion method against C. acnes, while antioxidant activity was assessed using the DPPH radical scavenging assay. The results demonstrated that all variations of the CMT oil combinations exhibited moderate antibacterial activity and strong antioxidant activity, with IC₅₀ values ranging from 50 to 100 µg/mL. Based on the Taguchi analysis, the optimal combination for antibacterial activity was obtained at concentrations of 6% champaca oil, 0.4% massoia oil, and 5% tea tree oil. Meanwhile, the most optimal and stable antioxidant activity was achieved with the combination at concentrations of 75:100:100 ppm. In both assays, champaca oil was identified as the most influential factor affecting the observed biological responses. These findings indicate that the CMT oil combination has promising potential as a multifunctional therapeutic candidate for cosmetic and pharmaceutical applications, particularly as a topical nanoemulsion face mist for the management of acne while simultaneously preventing skin damage caused by free radicals.